Transforming Indonesia’s Climate Strategy: Analyzing Policy Shifts and Global-Local Dynamics Post-COP 26 - Muhammad Yamin; I Putu Arya Aditia Utama; Tuomo Rautakivi; Slamet Rosyadi; Agus Ganjar Runtiko (Universitas Muhammadiyah Yogyakarta, 2024)
This study examined how the Indonesian government responded to the outcomes of the major international climate conference, Conference of the Parties (COP) 26, and how that response affected the creation of national response plans. Indonesia, previously regarded as less ambitious in climate change mitigation, has now embraced a more proactive approach following COP26. The research seeks to evaluate the extent to which the COP26 agreement has prompted a more ambitious stance in Indonesia’s climate policies. By utilizing a descriptive qualitative method bolstered by a comprehensive examination of existing literature and secondary data from multiple sources, the analysis uncovered the substantial influence of the COP26 agreement on policy modifications in Indonesia. These adjustments served to reinforce efforts in crucial sectors, including forestry, agriculture, energy, transportation, and finance. Indonesia’s proactive measures to address climate change impact and its increased dedication to global climate initiatives were evident in these findings, indicating a change in the country’s policy direction.